Crosstalk between platelets and PBMC: New evidence in wound healing. (17th February 2016) - Nami, Niccolò; Feci, Luca; Napoliello, Luca; Giordano, Antonio; Lorenzini, Sauro; Galeazzi, Mauro; Rubegni, Pietro; Fimiani, Michele
Abstract: Platelet-derived products have proven useful in accelerating healing processes and tissue regeneration. However, despite their widespread use in clinical practice, the cellular and molecular mechanisms involved have not yet been completely clarified. Recent studies show that interaction between platelet gel (PG) and peripheral blood mononuclear cells (PBMC) can result in activation of PBMC and production of several cytokines involved in wound healing and tissue repair. The aim of our study was to analyze whether crosstalk between platelets and PBMC can influence wound healing by modulating release of VEGF, bFGF and IL-10 by PBMC. Cultures of PBMC alone and co-cultures with autologous PG of 24 healthy volunteers were incubated under normoxia for 24 h. VEGF, bFGF and IL-10 concentration and expression were then analyzed in supernatants by ELISA and by real-time RT-PCR. We observed a down-regulation of VEGF and bFGF release and an up-regulation of IL-10 release in co-cultures of PBMC and PG. Platelets are not only important in the early stages of the healing process (clot formation, direct release of growth factors), but also can influence the whole process of tissue regeneration by modulating synthesis and release of VEGF, bFGF and IL-10 by PBMC. These effects could give platelets a new key role in the control of healing processes and provide insights into the clinical success of platelet-derived products in many medical fields.